Evaluation of Inkjet Ink and Substrate Degradation in Media with Varying pH Levels - Gokhale , C; Mali , B; Sood, A; Kaur, R (Journal of Indian Academy of Forensic Medicine, 2024)
Forensic questioned document is a very important field. Forensic document expert (FDE) are generally well versed with the characteristics  related to paper, ink and other writing media that helps in evaluating the case. Despite to possess great knowledge and experienced, a  forensic document examiner may deals with the lot of challenges. Documents reach the forensic document examiner in different and  various conditions. The documents can be torn, shredded, burnt, chemically destroy, engrave in soil or even soaked in some liquid. The  document may be thrown in ponds, water tanks etc. by the criminal in order to hide the original document. During a document comes in  contact with any liquid lots of destructive will happen to it. Many techniques are attempted and proposed for examination of water soaked  documents and if required the restoration of content. Therefore, the present study has been attempted to evaluate the impact of soaking in  different liquid medium on the different paper surfaces and printed content. The printed document soaked in liquids having different pH  (Acidic, basic, neutral) were studied so as to determine the effect on printing ink and substrate. The change in characteristics of the paper  and ink were noted and facilitated in estimating the age of the soaked document. The samples were examined using Olympus  Stereomicroscope and under Ultra-violet light.
Keywords: Bond paper; Glossy paper; Soaked document; UV light; Stereomicroscope; Inkjet printer; Questioned documents